Dampak Pengaturan Pembatasan Jumlah Calon Kepala Desa Pasca Lahirnya Undang-Undang Nomor 6 Tahun 2014 - Monica Puspa Dewi; Kuni Nasihatun Arifah; Alan Bayu Aji (LPPM Universitas Harapan Bangsa, 2023)
One form of Village Democracy is the Election of Village Heads, since the design of the Election of Village Heads has been carried out directly. Villagers can directly elect Village Head Candidates, but the latest development is that there are rules limiting the number of village head candidates to a minimum of two people and a maximum of five people. The purpose of this research is to examine the regulatory impact of limiting the number of village head candidates. This research is a type of empirical normative legal research with a conceptual approach. Based on the results of this study, it shows that there are two impacts, namely the regulatory impact if the number of candidates is not fulfilled can be postponed, then the social impact is the appearance of a husband and wife candidate for village head.